Built in electric field boosted photocatalytic performance in a ferroelectric layered material SrBi2Ta2O9 with oriented facets: Charge separation and mechanism insights. (1st October 2022) - Liao, Biru; Liao, Xiaomin; Xie, Huiyuan; Qin, Yuanchu; Zhu, Yi; Yu, Yang; Hou, Sen; Zhang, Yuanming; Fan, Xiaoyun
Highlights: · A SrBi2 Ta2 O9 ferroelectric sample with exposed facet is synthesized. · SrBi2 Ta2 O9 with {001} facet is 138 times of the pristine one for CIP degradation. · Built-in electric field along polarization direction promotes charge separation. · The possible degradation pathways and intermediates toxicity are analyzed. Abstract: Antibiotics have received increasing attention due to their potential adverse effects on aquatic life and human health. How to efficiently degrade them into harmless substances is a challenging subject. Ferroelectric materials with a built-in electric field can offer a strong separation ability for the photoinduced-charge pairs and are now found to be used as photocatalysts. Herein, a series of different morphologies of SrBi2 Ta2 O9 ferroelectric photocatalysts with high antibiotic degradation efficiency have been successfully synthesized through a molten salt method. With the addition of KCl, SrBi2 Ta2 O9 (SBTO 3) with exposed (001) facets shows the most excellent photocatalytic activity for decomposing tetracycline (TC) and ciprofloxacin (CIP) under visible light illumination ( λ > 420 nm). The rate constants of SBTO 3 for TC and CIP degradation are 1.38 × 10 –1 and 4.54 × 10 –2  min –1, which are 18 and 138 times that of the unmodified sample, respectively. The enhancement of photocatalytic performance is mainly attributed to the spontaneous polarization electric field along the [001] direction which provides a strong driven force for the separation of photoinduced charges. The KPFM results also confirm that the superior photocatalytic activity is consistent with the big large surface potential changes before and after light irradiation. The possible degradation pathways and intermediates of TC and CIP were well analyzed by DFT calculation and LC-MS. The results highlight that morphology control of the ferroelectric materials exhibits enhanced photocatalytic performance for the degradation of the antibiotic. Graphical abstract: Two antibiotics, tetracycline and ciprofloxacin, can be degraded into small molecules efficiently by one type of Aurivillius-type layered ferroelectric material SrBi2 Ta2 O9 under visible light irradiation. Image, graphical abstract